2018
DOI: 10.5755/j01.ee.29.1.16400
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in financial behaviours

Abstract: The assessment of the impact of gender on financial decision-making was based on a representative survey 'Social Diagnosis 2015' conducted on a sample of over 34 thousand Polish citizens. When realising the research objective, a logistic regression model was appliedboth with and without interaction effects. The study has shown that the financial behaviours of men and women differ significantly. Men more frequently use the products and services available on the financial market such as, for instance, a debit ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
2
21
1
1
Order By: Relevance
“…Walczak, Pienkowska-Kamieniecka et al [11]- [13] suggested that differences indeed exist in the wealth management habits and investment behaviors of genders. The main difference lies in the fact that males are more inclined to choose bold investment projects, while women are more conservative, and in favor of medium-term and long-term stable investment.…”
Section: Research Motives and Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…Walczak, Pienkowska-Kamieniecka et al [11]- [13] suggested that differences indeed exist in the wealth management habits and investment behaviors of genders. The main difference lies in the fact that males are more inclined to choose bold investment projects, while women are more conservative, and in favor of medium-term and long-term stable investment.…”
Section: Research Motives and Purposesmentioning
confidence: 99%
“…Byrnes, Miller, and Schafer [14] suggested that there are differences in risk taking between men and women. Walczak and Pienkowska-Kamieniecka [11] pointed out that there are significant differences in financial behaviors between men and women. Men use products and services available in the financial market more frequently, such as debit cards, or investment in stocks or bonds.…”
Section: ) Difference Of Risk Appetitementioning
confidence: 99%
“…To select an appropriate internet financial product, firstly, we need to establish a criteria system, and then the performance of alternatives can be evaluated according to these criteria. In this regard, many studies about internet financial product selection focused on the factors that influence consumer choice (Cai et al, 2015) and consumer behavior (Zhai & Huang, 2016;Walczak & Pienkowska-Kamieniecka, 2018). Cai et al (2015) pointed out that the return rate, liquidity, threshold height, capital security, policy risk, and convenient payment can be taken as the factors from the consumer perspective.…”
Section: Criteria System Establishment For Internet Financial Productmentioning
confidence: 99%
“…For example, both generations spend much money for today, although Zs are perceived as a generation who tends to save, while Ys typically do not care about their savings (Bencsik et al, 2016). Traynor (2015) demonstrated preferences of making savings by these generations. House, travel, and further education are highly preferred, while retirement or having children have low preferences.…”
Section: Introductionmentioning
confidence: 99%